(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2014)
It is quite obvious that recognition of prior learning (RPL) (“validering” in Swedish) has not been commonly used as a method by the Swedish labor market organizations. Instead, RPL has most often been a method used in order to assess and visualize vocational knowledge and skills of the unemployed. There are several answers to that, e.g., the employers do not find enough reasons to invest in the formalization of the skills already in use within the organization (Berglund & Andersson, 2012). The objective of this article is to, by the help of a model previous developed by Ellström (1992; 1997), the Occupational Competence and Qualifications Model, illustrate the relationship between the impact of traditional RPL activities and the organization’s own internal assessment activities. The developed model shows the explicit and implicit aspects of knowledge and competence both used and not used within the organization. The model points to the difficult task in bringing informal skills to the surface, something that is not always in everyone’s interest. Another main focus of the article is to point to what might be a key motivational factor for the employer in using RPL activities directed to their staff.